Regional Economic Outlook, October 2019, Middle East and Central Asia. (Regional Economic Outlook, 2019)
Growth in the near term remains subdued for oil exporters in the Middle East, North Africa, Afghanistan, and Pakistan (MENAP) region, amid volatile oil prices, precarious global growth, elevated fiscal vulnerabilities, and heightened geopolitical tensions. In addition, declining productivity is dampening medium-term growth prospects. To reduce dependence on oil prices and pave the way for more sustainable growth, fiscal consolidation needs to resume, underpinned by improved medium-term fiscal frameworks. In parallel, structural reforms and further financial sector development would boost foreign direct investment (FDI) and domestic private investment and foster diversification, thus contributing to improved productivity and potential growth.